MARKETING STRATEGY FOR STREET FOOD VENDORS IN CIDU MARKET, MAKASSAR - Rahmadhani Rahman; Marhawati Najib, Muhammad Jufri (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2024)
This research aims to examine the marketing strategies implemented by street vendors, specifically food vendors selling suki-suki at Cidu Market in Makassar, with the goal of increasing their sales revenue. Therefore, the researcher aims to conduct an in-depth analysis of the Marketing Strategy of Suki-suki Street Food Vendors at Cidu Market in Makassar. The research method used is a qualitative exploration method with SWOT analysis as its framework. The results of this study indicate that based on the analysis using the previously processed and presented SWOT diagram, the data analysis shows that the Suki-Suki business is in quadrant I, which is dynamic growth or a strategic position of strength-opportunity. In other words, it uses its strengths to take advantage of opportunities in decision-making. This indicates that there is an opportunity to develop the Suki-Suki food business, where it not only has greater strengths than weaknesses but also has greater opportunities than threats